Structural breaks and cointegration analysis in the EU developed markets - Ferreira, N. (2013)
The strategic positioning of European economies, namely interest rate fluctuations, stock market crises, regional effects of oil prices and regional political developments make them vulnerable to real and external shocks. First signs of a sovereign debt crisis spread among financial players in the late 2009 were a result of the growing private and government debt levels worldwide. In an established crisis context, it was searched for evidence of structural breaks and cointegration between interest rates and stock market prices in the developed European markets under stress along a 13 year time-window. The results identified significant structural breaks at the end of 2010 rejecting the null hypothesis of no cointegration, and this resulted in its spread from the US to the rest of the world.